Concept and Making of Aqidah Learning Curriculum at Pondok Modern Darussalam Gontor - Mukri, Rusdiono; Hafidhuddin, Didin; Bahruddin, E.; Indra, Hasbi (Journal of Psychology and Sustainable Education, 2025)
This research aims to discover the concept and making of the aqidah learning curriculum at Pondok Modern Darussalam Gontor. This study uses a qualitative approach with a descriptive method. The primary data source of this research was obtained through direct observation at the research site and interviews with key informants from the leadership of Pondok Modern Gontor. This team compiled the aqidah learning curriculum and Gontor alums. Meanwhile, secondary data is obtained from indirect sources such as documents, books, magazines, journals, and other documentation. The study results show that the learning of aqidah in Gontor is developing in line with the challenges faced at the time. In the early days of Gondor's establishment, aqidah learning used aqidah books, which only existed in two classes, namely in grade 1 and grade 2. Around the 1990s, books for grades 5 and 6 were added. Then, the next one is added again for grade 4. As for grade 3, there are still no books. When this research was carried out, the Pondok Modern Gontor aqidah learning curriculum team planned to compile a book that would be used for aqidah learning in grade 3. So far, the material for grade 3 is Islamic taqiyah material, not aqidah material.